(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Previous authors have described the adult Diaspididae (Coccoidea) antenna as bearing very few or no strutures. But a recent paper demonstrated the full sensory function of the small seta placed on the adult female antenna of Diaspis echinocacti. In arder to clarify the nature of the female antenna, this paper discusses the question of formation of the uniarticulate second instar antenna as it is tranformed from the six-segmented first instar antenna. Based on interpretation of the results of amputation experiments, the authors hypothesize that the uniarticulate second instar antenna is formed as a result of a fusion of all the articles of first instar antenna. It is suggested that this fusion process is common to ali Diaspididae. This study suggests that we should indague on the adult female antenna in others species of Diaspis 1828 for joined seta, and eventually to evaluate the importance of the character into the systematic of the taxon. We further suggest that the adult female of other Diaspis species should be exarnined to evaluate the importance of antennal structures as characters that can be used in systematics.